PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA KARYAWAN DI PT. PEGADAIAN (PERSERO) KANTOR WILAYAH 1 MEDAN (LAYANAN JASA) - Tampubolon, Indra Gani; Sari, Sindi Kumala; Tarigan, Avinda Deviana Br; Manihuruk, Desi Dosiana (JURNAL GLOBAL MANAJEMEN; Vol 8 No 1 (2019): JUNI, 2019)
Human resource competence and training has the usefulness that must be noted on career planning, especially for long-term employees in helping to face greater responsibility in the future. This research was conducted at PT. Pegadaian Regional Office 1 Medan with the amount of sample taken in this study amounted to sixty seven (67) persons.This research applied quantitative research method. The result of the research simultaneously showed that Competency and Training had positive and significant effect on employees’ performance which was as much as (8.545> 2.35) with a significant level of 0.000> 0.05. Partially Competence effect had t count of 2,009 and ttable value of 1.66039, the value of t count > t table was as much as (2,009> 1.66039) with a significant value of 0.049> 0.05.